Frontal theta reveals further information about neural valence-dependent processing of augmented feedback in extensive motor practice. - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Spielplatzgeräte: Potenziale zur ganzheitlichen Förderung von Heranwachsenden - Strotmeyer, Anne; Ortwein, Lena; Kehne, Miriam (Playground@Landscape)

The science of deceptive human movement - Güldenpenning, Iris; Jackson, Robin C.; Cañal-Bruland, Rouwen (Human Movement Science)

Learning and Memory in Sports - Weigelt, Matthias; Krause, Daniel; Güldenpenning, Iris (Sport and Exercise Psychology)

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Routing in Hypergraphs - Deppe, Volker

Parallele Universen des Wissenschaftsmanagements? Ein Vergleich des Wissenschaftsmanagements an Hochschulen und außeruniversitären Forschungseinrichtungen in Deutschland. - Schneider, Sebastian; Mauermeister, Sylvi; Henke, Justus; Aust, Robert (Hochschulmanagement. Zeitschrift für die Leitung, Entwicklung und Selbstverwaltung von Hochschulen und Wissenschaftseinrichtungen.)
The development of good conditions for research is an essential task of research institutions, which in practice is nowadays mostly performed by science managers. Research in the field of science management in Germany mainly refers to developments at universities, whereas little is known about the situation at so called non-university research organisations. At the same time, there are hardly any statistics on the size of the science management in Germa-ny. In order to take first steps towards exploring these parallel universes, this article presents a comparative mapping of science management at universities and non-university research organisations for Germany by drawing on a special analysis of the German Federal Statistical Office and an online survey.

Citizen Science: Laien-Partizipation an Forschung - Göbel, Claudia; Henke, Justus; Mauermeister, Sylvi; Pasternack, Peer (Wissenschaftskommunikation, neu sortiert.)

Gesellschaftlich-demokratische Teilhabe: trotz hochschulischer oder durch hochschulische Bildung? - de Angelis, Moira; Harles, Dorothea; Mauermeister, Sylvi; Aust, Robert (Das Hochschulwesen)

Multirate Discrete Mechanics and Optimal Control for a Flexible Satelite Model - Lishkova, Yana; Ober-Blöbaum, Sina; Leyendecker, Sigrid

Variational approach for modelling and optimal control of electrodynamic tether motion - Lishkova, Y.; Bando, M.; Ober-Blöbaum, Sina

Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Virtual Reality Collaboration Platform for Agile Software Development - Yigitbas, Enes; Witalinski, Iwo; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 24th International Conference on Product-Focused Software Process Improvement (PROFES 2023))

The influence of effort instructions on the production of head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Kunde, Wilfried; Güldenpenning, Iris (Human Performance – Assessment, Intervention & Analysen. Abstractband der 55. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))
Keywords: Perception; Action Preparation; Cognition

The influence of effort instructions on producing head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Güldenpenning, Iris (Abstracts of the 65th Conference of Experimental Psychologists (TeaP))
Keywords: perception; action preparation; movement planning; effort instructions

Transferability of a discrepancy model for the dynamics of electromagnetic oscillating circuits - Wohlleben, Meike Claudia; Muth, Lars; Peitz, Sebastian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics)
Modelling of dynamic systems plays an important role in many engineering disciplines. Two different approaches are physical modelling and data‐driven modelling, both of which have their respective advantages and disadvantages. By combining these two approaches, hybrid models can be created in which the respective disadvantages are mitigated, with discrepancy models being a particular subclass. Here, the basic system behaviour is described physically, that is, in the form of differential equations. Inaccuracies resulting from insufficient modelling or numerics lead to a discrepancy between the measurements and the model, which can be compensated by a data‐driven error correction term. Since discrepancy methods still require a large amount of measurement data, this paper investigates the extent to which a single discrepancy model can be trained for a physical model with additional parameter dependencies without the need for retraining. As an example, a damped electromagnetic oscillating circuit is used. The physical model is realised by a differential equation describing the electric current, considering only inductance and capacitance; dissipation due to resistance is neglected. This creates a discrepancy between measurement and model, which is corrected by a data‐driven model. In the experiments, the inductance and the capacity are varied. It is found that the same data‐driven model can only be used if additional parametric dependencies in the data‐driven term are considered as well.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Evaluation of Physics Textbooks - Kapanadze, Marika; Jonas-Ahrend, Gabriela; Mazzolini, Alexander; Joubran, Fadeel (The International Handbook of Physics Education Research: Special Topics)
Physics textbooks are generally viewed as important tools that provide well-presented and reliable information that supports and enhances students' understanding of critical concepts. The main goal of this chapter is to find out what attention has been given to textbook evaluation in physics education research literature. Studies about physics textbooks from different countries and different eras are discussed and analyzed, and a broad overview about aspects that influence the efficacy of physics textbooks are presented. Research papers that discuss the importance and influence of digital textbooks (and similar technological resources) are also analyzed.